Computational fluid dynamic analysis of the effect of inlet valve closing timing on common rail diesel engines fueled with butanol–diesel blends - Lamani, Venkatesh T.; Shivaprasad, K. V.; Roy, Dibyendu; Yadav, Ajay Kumar; Kumar, G. N. (Frontiers in Energy Research, 2024)
The inlet valve closing (IVC) timing plays a crucial role in engine combustion, which impacts engine performance and emissions. This study attempts to measure the potential to use n-butanol (Bu) and its blends with the neat diesel in a common rail direct injection (CRDI) engine. The computational fluid dynamics (CFD) simulation is carried out to estimate the performance, combustion, and exhaust emission characteristics of n-butanol–diesel blends (0%–30% by volume) for variable valve timings. An experimental study is carried out using standard valve timing and blends to validate the CFD model (ESE AVL FIRE). After validation, the CFD model is employed to study the effect of variable valve timings for different n-butanol–diesel blends. Extended coherent flame model-3 zone (ECFM-3Z) is implemented to conduct combustion analysis, and the kappa–zeta–f (k–ζ–f) model is employed for turbulence modeling. The inlet valve closing (IVC) time is varied (advanced and retarded) from standard conditions, and optimized valve timing is obtained. Advancing IVC time leads to lower cylinder pressure during compression due to reduced trapped air mass. The brake thermal efficiency (BTE) is increased by 4.5%, 6%, and 8% for Bu10, Bu20, and Bu30, respectively, compared to Bu0. Based on BTE, optimum injection timings are obtained at 12° before the top dead center (BTDC) for Bu0 and 15° BTDC for Bu10, Bu20, and Bu30. Nitrogen oxide (NOx) emissions increase due to complete combustion. Due to IVC timing, further carbon monoxide and soot formation decreased with blends and had an insignificant effect.